2021
DOI: 10.1038/s41598-021-98666-6
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of microwave absorption properties of polyester coatings using NiFe2O4, X-doped g-C3N4 (X = S, P, and O), and MTiO3 (M = Fe, Mg, and Zn) nanofillers

Abstract: In recent decades, to reduce electromagnetic pollution, scientists focus on finding new microwave absorbers with effective performance, thin thickness, and broad bandwidth. In this work, the nanoparticles of NiFe2O4, X-doped g-C3N4 (M = S, P, and O), and MTiO3 (M = Fe, Mg, and Zn) were successfully synthesized using co-precipitation, specific heat program, and semi-wet sol–gel methods, respectively. The synthesized nanoparticles were utilized as absorption agents and polyester resin as the matrix. Morphology, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Z N , Z in , Z 0 exhibit the ability of the electromagnetic wave to enter the absorber, input impedance, and impedance of free space, respectively. The maximum value for Z N is 1 which exhibits the ideal impedance matching 18 . Z N is expressed as follows 19 : ZnormalN=ZinZ0=μnormalrεnormalrtanhj2italicπfdcμnormalrεnormalr. …”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Z N , Z in , Z 0 exhibit the ability of the electromagnetic wave to enter the absorber, input impedance, and impedance of free space, respectively. The maximum value for Z N is 1 which exhibits the ideal impedance matching 18 . Z N is expressed as follows 19 : ZnormalN=ZinZ0=μnormalrεnormalrtanhj2italicπfdcμnormalrεnormalr. …”
Section: Resultsmentioning
confidence: 98%
“…The maximum value for Z N is 1 which exhibits the ideal impedance matching. 18 Z N is expressed as follows 19 :…”
Section: Microwave Absorption Propertiesmentioning
confidence: 99%
“…After that, the precipitate is thermally processed to create oxygen-doped g-C 3 N 4 . 16 Solgi et al 16 fabricated O@g-C 3 N 4 using the same process and used oxalic acid as the oxygen source.…”
Section: Synthesis Techniques For Fabrication Of O@g-c3n4mentioning
confidence: 99%
“…As one of the titanium‐based perovskite oxides, ZnTiO 3 has attracted widespread attention in different frontier research fields due to its extraordinary potentials in electrode materials, [8] magnetic materials, [9] antibacterial materials, [10] gas sensors, [11] photocatalysis, [12,13] and heterogeneous catalysis [14,15] . It has been reported that cubic and hexagonal phases of ZnTiO 3 as catalyst support exhibit different catalytic performances in the steam reforming of methanol due to their different properties [14] .…”
Section: Introductionmentioning
confidence: 99%